2002
DOI: 10.1111/j.0004-8666.2002.548_15.x
|View full text |Cite
|
Sign up to set email alerts
|

Delays in diagnosing breast cancer – the impact of concurrent pregnancy and lactation

Abstract: 1 Browse NL, Whimster I, Stewart G, Helm CW, Wood JJ. Surgical management of 'lymphangioma circumcriptum'. Br J Surg. 1986 Jul; 73 (7): 585-588. 2 Fox T, Fox TC. On the case of lymphangiectodes with an account of the histology of the growth. Trans Path Soc, London. 1978; 30: 470-475. 3 Morris M. Lymphangioma circumscriptum. In: Unna PG, Morris M, Duhring LA, Leloir H, editors. International atlas of rare skin diseases. London; HK Lewis: 2. 4 Peachey RD, Lim CC, Whimster IW. Lymphangioma of the skin. A review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Most breast masses during pregnancy and lactation are found by the patient or provider rather than mammography 3,13 . When a woman presents with a breast mass during pregnancy and lactation, PABC must be included among differential diagnoses 9 . Some women are delaying child‐bearing into the perimenopausal years when breast cancer is more prevalent; therefore, it is likely a health care provider will encounter PABC in their practice 38 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most breast masses during pregnancy and lactation are found by the patient or provider rather than mammography 3,13 . When a woman presents with a breast mass during pregnancy and lactation, PABC must be included among differential diagnoses 9 . Some women are delaying child‐bearing into the perimenopausal years when breast cancer is more prevalent; therefore, it is likely a health care provider will encounter PABC in their practice 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of almost 5 million women who delivered an infant between 1991 and 1999 in California found that breast cancer was the most frequently occurring cancer in the obstetric population, with an incidence of 19.3 per 100,000 births 4 . Although the number of cases may not seem high, women with PABC suffer a poor prognosis 1,5–10 . Compared with women who are not pregnant or lactating, women with PABC are younger, have higher rates of estrogen receptor negative tumors (ER‐), and have high histological grade tumors—all which lead to greater risk of mortality 4,11,12 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite disease-related liver dysfunction, the authors report a successful use of a multi-drug regimen, with adapted doses and omission of methotrexate. The diagnosis of breast malignancies duringpregnancyisoftendifficult,andadelayindiagnosisisfrequent [9]. For instance, in one series from the M.D.…”
mentioning
confidence: 99%